Thinking about physics - Newton, Roger G (Princeton University Press, 2000)
"Newton's goal is to provide a framework within which the fundamental theories of modern physics can he explored, interpreted and understood." "Physics, according to Newton, has moved beyond the describing and naming of curious phenomena which is the goal of some other branches of science. Physicists have spent a great part of the twentieth century searching for explanations of experimental findings. Newton agrees that experimental facts are vital to the study of physics, but only because they lead to the development of a theory that can explain them. Facts, he argues, should undergird theory."--Jacket.